Fight Corruption the EU Membership Requirement: The Case of Albania - Balliu, Alesia (European Scientific Journal, ESJ, 2023)
Corruption is one of the most crucial challenges which emerges as a solid opponent to the universal rule of the law. This paper examines the issue of combating corruption in Albania and its significance in the context of the country's pursuit of EU membership. Drawing upon the political and juridical history of Albania, the study highlights the close link between political culture and combating corruption in Southeast Europe. It underscores the challenges faced by Albania in combating corruption due to its difficult political past and the shortcomings in the development and enforcement of the law. The implementation of the Justice Reform in Albania is recognized as a significant step toward combating corruption, but the process has encountered obstacles and delays. The paper emphasizes the importance of respecting the deadlines set for the reform and ensuring the functioning of the judicial system to safeguard citizens' rights. Recommendations are provided, including the need for a safety net to prevent critical vacancies in the judiciary, restraining the right to resign during vetting procedures, and ensuring adequate logistical support and independence for new judicial institutions. The study concludes by emphasizing the ongoing fight against combating corruption as an essential requirement for Albania's EU membership and the need for sustained efforts to address the shortcomings identified in the process.